Effectiveness of Moodle-Based E-Learning Development with the Addie Model in Vocational High Schools - Yolanda, Wira; Azhar, Viki; Giatman, M.; Effendi, Hansi; Novaliendry, Dony (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The utilization of technology in vocational education is crucial for overcoming the limitations of face-to-face learning and enhancing student competence. This study aims to analyze the implementation of a Moodle-based Learning Management System (LMS) developed using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model within Vocational High Schools (SMK). The method employed was a systematic literature review of 11 scientific articles published between 2016 and 2025. The analysis results indicate that the ADDIE model provides a structured framework to ensure the media's validity and feasibility. Moodle proved to be flexibly applicable across various expertise spectrums, ranging from Information Technology, Automotive Engineering, and Electrical Engineering to Office Administration. The main findings demonstrate that Moodle implementation consistently significantly improves student learning result, is considered valid by media and material experts, and receives positive responses from users. Recent trends in 2025 highlight the integration of Moodle with the Project-Based Learning (PjBL) model and the Computational Thinking (CT) approach to address industrial needs.